014 Wideband free breathing MOCO LGE changes patient care in patients with implantable cardiac defibrillators. (3rd April 2017) - Bhuva, Anish; Ramlall, Manish; Boubertakh, Redha; Knott, Kristopher; Feuchter, Patricia; Sekhri, Neha; Schilling, Richard; Kellman, Peter; Moon, James; Manisty, Charlotte
Abstract : Background: There is a growing need for CMR in patients with implanted devices, who represent a high-risk cohort. Recent reports suggest CMR may be safely performed but artefact remains a significant limitation to late gadolinium enhancement (LGE). It is still unknown whether novel sequences to reduce artefact can be used efficiently or provide clinically useful information from scar imaging. Methods: We used a novel free- breathing wideband MOCO sequence with PSIR (WB-MOCO) designed for a clinical environment. Patients with implantable cardiac devices (including MR non-conditional) referred clinically for CMR were scanned according to local standard operating procedure (based on national guidelines and Magnasafe Registry). WB-MOCO LGE approach was used primarily, with paired comparator conventional PSIR FLASH LGE or free breathing MOCO SSFP. Conventional and WB-MOCO LGE were assessed for artefact on a scale of 0 to 4 (0=no artefact, 4=completely obscured). A panel of three CMR cardiologists judged impact on patient care. Results: Of the 67 patients (age 54±19 years, 47 male), 17 had ICDs, 9 cardiac resynchronisation devices, 19 pacemakers and 22 implantable loop recorders (ILR). 20 (44%) pulse generators were non-conditional; 11 (16%) inpatients; 10 (15%) with AF; 7 (10%) pacing dependent. Every patient referred was scanned successfully. 10 leads had parameter changes by Magnasafe criteria with no clinical significance, and 80% normalising at follow up (66±40 days). With conventional LGE imaging, 22 (33%) scans were non-diagnostic. WB-MOCO LGE completely removed artefact in 19 (87%), and achieved diagnosis in the remaining 3. 10 (15%) patients had significant artefact on conventional LGE, which WB completely or almost completely removed. Overall, CMR with WB-MOCO LGE changed management in an additional 26 (39%) patients compared to CMR with conventional LGE (33 patients, 49%). This benefit was in 77% of defibrillators, 25% of pacemakers and 5% of the ILR groups. Conclusion: The WB-MOCO sequence permits high quality LGE imaging in device patients, and is robust enough for a clinical setting. This adds clinical utility particularly in defibrillator patients, also pacemaker patients but with limited utility in ILRs. Our electrophysiology department has now incorporated this into their protocol prior to ventricular tachycardia ablation.